Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2632-072x/aba8e1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical systems on hypergraphs

Abstract: We present a general framework that enables one to model high-order interaction among entangled dynamical systems, via hypergraphs. Several relevant processes can be ideally traced back to the proposed scheme. We shall here solely elaborate on the conditions that seed the spontaneous emergence of patterns, spatially heterogeneous solutions resulting from the many-body interaction between fundamental units. In particular we will focus, on two relevant settings. First, we will assume long-ranged mean field inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 67 publications
(55 reference statements)
3
66
0
Order By: Relevance
“…Indirect interactions-either higher-order interactions between species, or interaction strengths that themselves interact-have gained interest in recent years [172,173]. One mathematical tool to describe these situations is hypergraphs: hypergraphs are the generalization of a graph, allowing a broad yet manageable approach to complex interactions [174], by allowing for particular interactions to occur beyond a pair of nodes. An additional degree of complexity is introduced by multilayer networks [175].…”
Section: (V) How Do We Determine What Interaction Networkmentioning
confidence: 99%
“…Indirect interactions-either higher-order interactions between species, or interaction strengths that themselves interact-have gained interest in recent years [172,173]. One mathematical tool to describe these situations is hypergraphs: hypergraphs are the generalization of a graph, allowing a broad yet manageable approach to complex interactions [174], by allowing for particular interactions to occur beyond a pair of nodes. An additional degree of complexity is introduced by multilayer networks [175].…”
Section: (V) How Do We Determine What Interaction Networkmentioning
confidence: 99%
“…Indirect interactions-either higher-order interactions between species, or interaction strengths that themselves interact -have gained interest in recent years (Golubski et al 2016;Golubski and Abrams 2011). One mathematical tool to describe these situations is hypergraphs: hypergraphs are the generalization of a graph, allowing a broad yet manageable approach to complex interactions (Carletti, Fanelli, and Nicoletti 2020), allowing for particular interactions to occur beyond a pair of nodes. An additional degree of complexity is introduced by multi-layer networks (Hutchinson et al 2019).…”
Section: What About Indirect and Higher-order Interactions?mentioning
confidence: 99%
“…Recent works have focused on investigating dynamics on higher-order topologies [4], and a variety of dynamical processes such as diffusion [3,24], synchronization [27] or social and opinion dynamics [7,16,23] have been extended to multi-body frameworks. As a result, it was shown that higher-order interactions can significantly modify the dynamical process in comparison to the dynamical process on the underlying reduced network.…”
Section: Dynamics On Hypergraphsmentioning
confidence: 99%